The role of different nutrients in the prevention and treatment of cardiovascular diseases - Tu, Zhi; Yang, Jinfu; Fan, Chengming (Frontiers in Immunology, 2024)
Cardiovascular health is a hot topic around the world, and as the incidence of cardiovascular disease increases each year, people are increasingly focusing on the management of their heart health. Dietary and lifestyle changes as non-pharmacological treatments have been increasingly recognized as important in the prevention of cardiovascular disease and in reducing the risk of cardiovascular accidents. Awareness of different nutrients and their effects on cardiovascular health is important for establishing a good dietary pattern. This review summarizes the effects of the five major nutrients in the daily diet, namely carbohydrates, proteins, dietary fats, vitamins, and minerals, on cardiovascular health, and aims to provide a more comprehensive understanding of the effects of a healthy dietary pattern on cardiovascular health.